Influence of parental resilience on non-suicidal self-injury in adolescent cancer patients - Huang, Xiang; Li, Huiyun; Wu, Miaomiao; Chen, Zheng; Sang, Yufei (Frontiers in Psychiatry, 2025)
ObjectiveTo examine the effect of a structured, DBT-based parental resilience training program on non-suicidal self-injury (NSSI) and related psychological symptoms in adolescents with cancer.MethodsThis pre–post study without a control group enrolled 38 adolescent cancer patients (aged 13–18) with a history of NSSI, along with one of their parents. From March 2023 to May 2024, parents participated in a 4-week intervention consisting of three structured skills-training sessions (90 minutes each), weekly family group skills training, ongoing telephone counseling, and weekly consultations with a psychological support team. The Ottawa Self-Injury Scale was used to assess NSSI recurrence in adolescents. Anxiety and depression symptoms in adolescents were measured using the Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire (PHQ-9). Parental resilience was evaluated with the Connor-Davidson Resilience Scale (CD-RISC).ResultsAll administered questionnaires were fully completed and valid, yielding a 100% response rate. Following the 4-week intervention, the recurrence rate of NSSI was 13.16% (5/38). Adolescents demonstrated significant reductions in both GAD-7 and PHQ-9 scores from pre- to post-treatment (P < 0.05), indicating marked improvements in anxiety and depression symptoms. Parental CD-RISC scores increased significantly (P < 0.05), reflecting enhanced resilience. Subgroup analyses revealed that these improvements were significant across both genders and age groups (<15 years vs. ≥15 years), with no statistically significant differences in the magnitude of change between subgroups (P > 0.05).ConclusionsA short-term, DBT-based parental resilience training program may improve caregiver resilience, reduce adolescent anxiety and depression, and lower short-term NSSI recurrence in adolescents with cancer. However, the lack of a control group and short follow-up limit the generalizability of findings. Further controlled studies with larger samples and longer follow-up are warranted.